Effect of Transferrin‐Modified Fe3O4 Nanoparticle Targeted Delivery miR‐15a‐5p Combined With Photothermal Therapy on Lung Cancer - Xiaoxu Lan; Xiao Wang; Liying Shao; Jiayue An; Simin Rong; Xiancong Yang; Hongfang Sun; Yan Liang; Ranran Wang; Shuyang Xie; Youjie Li (Thoracic Cancer)
ABSTRACT Background Existing studies have shown that transferrin receptor (TfR) is highly expressed on the surface of lung cancer cells, and nanoparticles (NPs) have been widely used as delivery vehicles. The aim of this study was to investigate the effect of the targeted delivery of Fe3O4 NPs modified with transferrin (Tf) compared with photothermal treatment for lung cancer. Methods The morphology and properties of Fe3O4 NPs modified with Tf were tested by internal morphological characterization experiments including transmission electron microscopy, particle size meter infrared spectrometer and other experiments. The delivery of materials was investigated by cell proliferation and apoptosis experiments, and western blot experiment was used to detect yes‐associated protein 1(YAP1) protein expression changes after delivering miR‐15a‐5p. In addition, animal models were constructed to further explore the targeting properties of the material. Results The results demonstrated that the nanomaterial has good stability and targeting properties. Meanwhile, we also discovered that the miR‐15a‐5p carried by NPs can inhibit cell growth after its entry to the lung cancer cells. The effect became more evident when the nanomaterials were assisted with laser therapy, as verified by in vivo and in vitro experiments. In terms of the related mechanism, miR‐15a‐5p inhibited YAP1 expression, which affected cell proliferation and apoptosis. Conclusion In this study, Fe3O4 NPs modified with Tf delivered miR‐15a‐5p in combination with photothermal therapy for lung cancer. In future research, the targeted delivery of Tf and the photothermal synergy of nanomaterials will provide a theoretical basis for cancer treatment.